Early Analgesic Efficacy of Morphine, Butorphanol, Lidocaine, Bupivacaine or Carprofen After Periodontal Treatment in Dogs - Raušer, Petr; Fichtel, Tomáš (Journal of veterinary dentistry, 2020)
The early effectiveness of 5 analgesics was investigated after periodontal treatment. Dogs were assigned to 6 groups (n = 14 each). A prospective, randomized and blinded clinical study was performed. Before anesthesia was induced, butorphanol, morphine, carprofen and saline were administered. After induction, a maxillary and mandibular block was performed with lidocaine or bupivacaine. Painful periodontal therapies were performed. Two hours after the administration of analgesics and after anesthesia reversal, pain was scored using the Visual Analog Scale for pain (VAS) and the modified University of Melbourne Pain Score (UMPS). Blood glucose and cortisol levels were measured prior to analgesic administration and again 2 hours later. Rescue analgesia was provided when the VAS exceeded 50 mm or the UMPS exceeded 14 points. Rescue analgesia was required in one patient in the morphine group and one in the carprofen group. The VAS values were significantly lower in the butorphanol group compared to those of the saline group and in the bupivacaine group vs. those in the saline and lidocaine groups. Significantly lower UMPS values were obtained in the bupivacaine group compared to those in the saline, butorphanol and lidocaine groups and in the carprofen group vs. those in the saline and lidocaine groups. Significantly higher serum cortisol values were found in the lidocaine group compared to those in the saline, bupivacaine and carprofen groups. Administration of carprofen or the use of nerve blocks with bupivacaine improved analgesia after periodontal treatment more than did butorphanol, morphine or nerve blocks using lidocaine.
Keywords: hysterektomie; Carbazoles; karbazoly; pooperační bolest; Bupivacaine; Hysterectomy; prospektivní studie; nemoci psů; Female; lidokain; analgetika; Lidocaine; psi; Analgesics; Prospective Studies; Double-Blind Method; butorfanol; zvířata; Butorphanol; morfin; ženské pohlaví; Dogs; Animals; bupivakain; Pain, Postoperative; Anesthetics, Local; anestetika lokální; dvojitá slepá metoda; Morphine; Dog Diseases